Human immunodeficiency virus lymphomas in the era of antiretrovirals: Is it finally time to change the discussion?. Issue 17 (23rd June 2016) - Gunthel, Clifford J.; Lechowicz, Mary Jo
Abstract : Currently, clinicians involved in the treatment of and research regarding lymphoma may want to look toward achieving the goal of a dual cure of human immunodeficiency virus and cancer in patients with lymphoma. In addition, the difficult issues of health care disparities, disease prevention, and long‐term survivorship need to be addressed in this population. See also pages 2689‐97